2019
DOI: 10.1016/j.compscitech.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of grafted CNT dispersion and of their stiffening of polyurethane (PU)

Abstract: Electroactive devices are developed for energy conversion purposes. In particular, polyurethanes (PU) are lightweight and flexible materials, which have demonstrated their ability to convert electrical energy into mechanical energy (actuation by electrostriction) and vice-versa (energy harvesting). It has been shown that energy conversion efficiency can be increased by incorporating carbon nanotubes (CNTs) into a PU matrix. The counterpart of this improvement is the stiffness increase, which in turn limits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Based on the scanning electron microscopy (SEM) images of PBT‐matrix composites, the evaluation of dispersion coefficient is performed via binarization process. [ 48–50 ] Figure 3 shows that the binarization process of SEM images for PBT‐matrix composites and the frequency density distribution of free‐path spacing between the Sb 2 O 3 particle surfaces in the composites filled with 3 wt% Sb 2 O 3 nanoparticles. The transformation of images undergoes image‐processing procedures, including binarization and filter treatment by image analysis software.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the scanning electron microscopy (SEM) images of PBT‐matrix composites, the evaluation of dispersion coefficient is performed via binarization process. [ 48–50 ] Figure 3 shows that the binarization process of SEM images for PBT‐matrix composites and the frequency density distribution of free‐path spacing between the Sb 2 O 3 particle surfaces in the composites filled with 3 wt% Sb 2 O 3 nanoparticles. The transformation of images undergoes image‐processing procedures, including binarization and filter treatment by image analysis software.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 4, d v10 represents the particle size of a filler with a volume below 10%, d v50 represents the particle size of a filler with a volume below 50%, and d v90 represents the particle size of a filler with a volume below 90%. Looking at the size of a hypothetical cluster of homogeneous particles, d [3,2] shows the average particle size of the surface area, which means that the particle shape of the particle group is the same, the total volume (weight) is the same, and the total surface area is the same. d [4,3] is the average volume particle size, which refers to the particle size of an imaginary particle group with the same particle shape, the same total volume and the uniform particle size of the same particles.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…At a volume fraction of 80% of mineral powder, the thickness of the structural asphalt layer decreases to 0.1 µm. In this study, the surface area average particle size d [3,2] is used as the average particle size of mineral powders, in which d L of limestone is 5.770 µm, d G of granite is 25.525 µm, d F of fly ash is 4.294 µm, and d C of coal gangue is 11.859 µm. Thus, the model parameter R can be obtained.…”
Section: Parameters Of the Four-phase H-mrp Model For Asphalt Masticmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al [18] conducted coarse-grained molecular statics simulations for studying the electrical properties of CNT thin films and found that the ratio of the mean projected CNT length over the film length is related to the hysteresis of resistance. Jomaa et al [19] evaluated the effect of CNTs on the mechanical properties of CNT/PU composites by analysing the CNT network morphology and found that the CNTs do not stiffen the composite much because of the waviness, but increases the modulus significantly when stretched.…”
Section: Introductionmentioning
confidence: 99%